Novel molecularly imprinted phenolic resin–dispersive filter extraction for rapid determination of perfluorooctanoic acid and perfluorooctane sulfonate in milk. (30th January 2023) - Ren, Jing; Lu, Yanke; Han, Yehong; Qiao, Fengxia; Yan, Hongyuan
Highlights: MIP-PR prepared at room temperature recognised PFOA and PFOS. MIP-PR had the advantages of large surface area, easy synthesis, and low cost. MIP-PR had large adsorption capacity, strong selectivity, and rapid mass transfer. MIP-PR-DFE allowed extraction of PFOA and PFOS from milk in 5 min. MIP-PR-DFE-LC-MS/MS provided a new idea for the analysis of PFOA and PFOS. Abstract: Perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) are emerging pollutants that threaten food safety. Herein, a rapid, accurate, and selective method for determination of PFOA and PFOS in milk was established by using new molecularly imprinted phenolic resin (MIP-PR) as the adsorbent of dispersive filter extraction (DFE) combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS). MIP-PR was synthesized at room-temperature using m-aminophenol, glutaraldehyde, and perfluorononanoic acid as the monomers, cross-linkers, and virtual templates, respectively, and exhibited rapid mass transfer (30 s), high selectivity (imprinted factors > 3.7), and large adsorption capacity (>54.6 mg/g). Compared with reported methods, the developed MIP-PR–DFE method is fast, selective, inexpensive, and shows good purification and enrichment efficiency. The proposed MIP-PR–DFE–LC-MS/MS exhibited low limits of detection (0.006–0.022 ng/mL), high recoveries (94.7–109 %), and good precision (RSDs ≤ 9.5 %). This study provides a new idea for the development of imprinted resin adsorbents for perfluorinated compound, and a new method for sample pretreatment for monitoring of PFOA and PFOS in food.